The Effect of Impurities on the Surface Melt of a Glacier in the Suntar-Khayata Mountain Range, Russian Siberia - Takeuchi, Nozomu; Fujisawa, Yuta; Kadota, Tsutomu; Tanaka, Sota; Miyairi, Masaya; Shirakawa, Tatsuo; Kusaka, Ryo; Fedorov, Alexander N.; Konstantinov, Pavel; Ohata, Tetsuo (Frontiers in Earth Science, 2015)
We investigated characteristics of impurities and their impact on the ablation of Glacier No.31 in the Suntar-Khayata Mountain Range in Russian Siberia during summer 2014. Positive degree-day factors (PDDFs) obtained from 20 stake measurements distributed across the glacier’s ablation area varied from 3.00 to 8.55 mm w.e. K-1 day-1. The surface reflectivity measured with a spectrometer as a proxy for albedo, ranged from 0.09 to 0.62, and was negatively correlated with the PDDF, suggesting that glacier ablation is controlled by surface albedo on the studied glacier. Mass of total insoluble impurities on the ice surface varied from 0.1 to 45.2 g m-2 and was not correlated with surface reflectivity, suggesting that albedo is not directly conditioned by the mass of the impurities. Microscopy of impurities revealed that they comprised mineral particles, cryoconite granules, and ice algal cells filled with dark-reddish pigments (Ancylonema nordenskioldii). There was a significant negative correlation between surface reflectivity and algal biomass or organic matter, suggesting that the ice algae and their products are the most effective constituents in defining glacier surface albedo. Our results suggest that the melting of ice surface was enhanced by the growth of ice algae, which increased the melting rate 1.6 - 2.6 times greater than that of the impurity free bare-ice.